2021
DOI: 10.35633/inmateh-63-22
|View full text |Cite
|
Sign up to set email alerts
|

A General Modelling Approach for Coated Cotton-Seeds Based on the Discrete Element Method

Abstract: In the current paper, a coated cotton-seed discrete element model was established. Furthermore, we designed a device for the simultaneous determination of the repose and accumulation angles, and Plackett–Burman and central composite design (CCD) tests were performed with the repose and accumulation angles as the test indexes. The static friction coefficient between seeds (SFCC) and the dynamic friction coefficient between seeds (DFCC) were observed to have a significant influence on the indexes and were thus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, according to the fact that the diameter of the commonly used metering wheel on the market is generally between 350 mm and 420 mm, the previous research of the project team and only the semicircle of the auxiliary wheel and the metering wheel is wrapped by the crawler, the diameter of the corresponding metering wheel and the auxiliary wheel of the device is set to 370 mm. According to the agronomic requirements and the common size of the current cotton dibbler, the cotton plant spacing was selected as 100 mm according to the reference [12][13][14]. It can be seen from Figure 2 that the number of duck bill that the track always contacts with the ground is 7, and the contact length between the track and the ground during the operation of the machine is always 700 mm.…”
Section: Structural Design Of Critical Componentmentioning
confidence: 99%
“…Therefore, according to the fact that the diameter of the commonly used metering wheel on the market is generally between 350 mm and 420 mm, the previous research of the project team and only the semicircle of the auxiliary wheel and the metering wheel is wrapped by the crawler, the diameter of the corresponding metering wheel and the auxiliary wheel of the device is set to 370 mm. According to the agronomic requirements and the common size of the current cotton dibbler, the cotton plant spacing was selected as 100 mm according to the reference [12][13][14]. It can be seen from Figure 2 that the number of duck bill that the track always contacts with the ground is 7, and the contact length between the track and the ground during the operation of the machine is always 700 mm.…”
Section: Structural Design Of Critical Componentmentioning
confidence: 99%
“…Joash Bryan Adajar [31] carried out a variety of shear tests between field residues and soil and found that the relative error was less than 2% through the measurements of the stress-displacement and friction angle, which is a better observation of the interaction mechanism between the straw and the soil. The interaction mechanism between straw and soil, in addition to modeling for Panax ginseng, sunflower seeds, rice, wheat, and so on [32][33][34][35][36][37][38][39][40], can show their respective contact characteristics relatively well. Some application scenarios of the Hertz-Mindlin (no-slip) contact model are shown in Figure 4.…”
Section: 𝛽 = 𝑙𝑛𝑒mentioning
confidence: 99%
“…Yunxia Wang, Fanyi Liu, and Tao Wu calibrated the discrete elemental model parameters of corn seeds, wheat, and clayey soil, respectively, based on angle of repose simulation experiments [6][7][8]; Xu Bing established a non-spherical particle model of buckwheat seeds using the auto-filling method and parameterized it using a discrete element model [9]. Wang Long designed a device to simultaneously determine the angle of repose and angle of accumulation of materials and calibrated the contact parameters of cotton seeds through physical and simulation tests [10]. Balevičius measured the static friction coefficient between pea and glass by sliding test [11].…”
Section: Introductionmentioning
confidence: 99%